Gender and arson: psychosocial, psychological, and somatic offender characteristics at the time of the crime - Andrén, Victoria (The journal of forensic psychiatry & psychology, 2023)
Deliberate fire-setting, such as the crime of arson, can have devastating, even lethal, consequences. This study compared factors at the time of arson by female and male offenders in Sweden between 2000–2010. The women (n = 100), and men (n = 100) included in this study were randomly chosen from among all individuals who had been convicted for arson during this period and who underwent forensic psychiatric investigations. Information regarding psychiatric and somatic characteristics, their psychosocial situation, and whether they were in contact with health or social services before the arsons were examined. The results showed that both women and men have complex psychiatric and somatic characteristics, as well as psychosocial situations. Women showed more self-destructive behaviour, lower Global Assessment of Functioning scores, and had been in contact with psychiatric health services to a greater extent than men. More women than men had children. These findings suggest that specific actions may be needed for preventing and treating women compared with men at risk for committing arson.